Analisis Organizational Citizenship Behavior Terhadap Kinerja Karyawan - Ikko Rosalia; Enny Diah Astuti (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to analyze Organizational Citizenship Behavior on employee performance. The sample in this study was employees which amounted to 65 employees with a total sampling technique. The analysis technique uses data Validity Test, Data Reability Test, Normality Classical Assumption Test, Simple Linear Regression Test, Partial T Test, Determination Test. The results showed that Organization Citizenship Behaviour on employee performance can be concluded that Organizatiion Citizenship Behaviour on employee performance has an influence based on the results of the calculation test of 4.942 > 1.998 with a significant value of OCB (x) on employee performance (y) is 0.00 < 0.05. Thus, drawing the conclusion H0 was rejected and Ha was accepted. The solution to the research barriers is carried out by collecting samples by collecting physical or paper media, distributing questionnaires at rest periods and using supporting devices for data processing.